The Conversion of Mary Rich, Countess of Warwick - Anselment, Raymond A. (Christianity & literature, 2017)
Religious conversion is basic to the narrative of Mary Rich’s life that she began writing in 1672. It is fundamental to her diary of many years. Where the autobiography emphasizes her marriage and the conversion that followed, the diary is an affirmation of that conversion and a reassessment of her marriage. Conversion brought Rich closer to God at the same time it affected what had become a troubled relationship with her husband. Concerned for his soul, and not only for her own, her diary offers a testimony of Mary Rich’s spiritual love for both her husband and God.